Eighteen years after Doha: An analysis of the use of public health TRIPS flexibilities in Africa - Yousuf A. Vawda; Bonginkosi Shozi (South Centre, 2020)
As we observe the 18th anniversary of the Doha Declaration on the TRIPS Agreement (Agreement on Trade-Related Aspects of Intellectual Property Rights) and Public Health, it is appropriate to take stock of intellectual property developments and endeavour to present a comprehensive account of the situation in the African continent in respect of the implementation of TRIPS flexibilities, specifically those regarding access to medicines. This research paper provides an overview of the extent to which selected African countries have adopted legal and policy frameworks with regard to TRIPS flexibilities, examines the actual use of these flexibilities in enabling access to medicines in those countries, and suggests some recommendations for optimising the use of the flexibilities in pursuing public health imperatives.
Keywords: 300; Access to Medicines; Affordable Medicines; Africa; African Regional Intellectual Property Organization (ARIPO); Bolar; Competition Law; Competition Policy; Compulsory Licenses; Doha Declaration on the TRIPS Agreement and Public Health; East African Community (EAC); Flexibilities; Government Use; Health; Industrial Property; Innovation; Intellectual Property; Least Developed Countries (LDCs); Parallel Imports; Patent; Patent Examination; Patent Linkage; Patent Term; Patentability Criteria; Post-Grant Opposition; Pre-Grant Opposition; Public Health; Research and Development (R&D); Research Exception; Southern African Development Community (SADC); TRIPS; TRIPS-Plus Provisions; World Trade Organization (WTO); WTO